2015
DOI: 10.1590/1678-4499.03914
|View full text |Cite
|
Sign up to set email alerts
|

Soil attributes under different crop management systems in an Amazon Oxisols

Abstract: Soil biological properties have a high potential for use in assessing the impacts of crop systems. The objective of this study is to evaluate the effects of cropping systems on the biological attributes of an oxisol in the Amazonian state of Pará. The treatments consisted of approximately 20-year-old secondary vegetation, recovered pasture, no-tillage systems (NT) maintained for 4 and 8 years after planting with corn (Zea mays L.) and soybean (Glycine max L.), and conventional tillage (CT) systems every 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In general, the average levels of K in the soil observed in this study were low (<0.05-0.10 cmol c kg −1 ), according to Moreira and Fageria [13] criteria. Soils in Amazonia hold low K contents [6,13,19,20] and, due to the relatively high demand many native plants have for it, K becomes one of the most limiting nutrients for Organic Fertilizers producing fruits in this region [21]. Studies conducted in the Manaus region have shown K to be the most exported nutrient through agroforestry products originating from Amazonian native species, such as cupuassu, peach palm (Bactris gasipaes), and assai (Euterpe oleracea), with higher concentration in shells, seeds, and infructescence petioles, which must be reincorporated into the planting areas to maintain sustainability [22].…”
Section: Exchangeable K Available P and Organic C Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the average levels of K in the soil observed in this study were low (<0.05-0.10 cmol c kg −1 ), according to Moreira and Fageria [13] criteria. Soils in Amazonia hold low K contents [6,13,19,20] and, due to the relatively high demand many native plants have for it, K becomes one of the most limiting nutrients for Organic Fertilizers producing fruits in this region [21]. Studies conducted in the Manaus region have shown K to be the most exported nutrient through agroforestry products originating from Amazonian native species, such as cupuassu, peach palm (Bactris gasipaes), and assai (Euterpe oleracea), with higher concentration in shells, seeds, and infructescence petioles, which must be reincorporated into the planting areas to maintain sustainability [22].…”
Section: Exchangeable K Available P and Organic C Contentsmentioning
confidence: 99%
“…The often wasted cupuassu tree fruit shells could be used in contributing to fertilize the soils. The recycling of these wastes, as well as a better use of natural resources, has become very important when it comes to sustainable agriculture since it reduces production costs and minimizes environmental impact [5,6]. Furthermore, organic residues can bear phytopathogenic suppressing microorganisms present in the soil, in addition to stimulating the growth of a more diversified and competitive/suppressing microbiota, reducing the occurrence of plant diseases [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies carried out in Amazon soils on N fractions in different agricultural systems investigated, in particular, total N (Silva Júnior et al, 2018) andmicrobial N (Aragã o et al, 2012;Lopes et al, 2015) for evaluation of the biological response given by the microbiota. The inorganic N fractions determination can help to better understand the potential N availability.…”
Section: Introductionmentioning
confidence: 99%
“…Soil management and practices must assure maintenance or enhancement of soil biological, chemical, and physical features, consequently providing sustainable production and crop yield (Lopes et al, 2015). Certain fractions of SOM play key role on maintaining soil quality, being more sensitive to management practice effects (Ebeling et al, 2011).…”
Section: Introductionmentioning
confidence: 99%